PD-1/PD-L1 inhibitor-related cystitis: clinical features, diagnostic exclusion, and outcomes in one definite and seven probable cases with an updated literature review - Wei Ding; Heqian Liu; Lin Li; Yingqing Liu; Jiawei Wang; Zhonglang Wang; Lingsong Tao; Xiansheng Zhang (Frontiers in Oncology, 2026)
Background PD-1/PD-L1 inhibitor-related cystitis (PD-(L)1-RC) is an uncommon urinary immune-related adverse event that may be mistaken for bacterial cystitis, tumor progression, radiation injury, stone disease, or chemotherapy-related hemorrhagic cystitis. This study describes the clinical phenotype, diagnostic exclusion process, treatment response, and updated literature context of PD-(L)1-RC. Methods We retrospectively reviewed eight patients who developed new lower urinary tract symptoms after PD-1/PD-L1 inhibitor-based therapy for malignancies during a prespecified clinical study period from January 1, 2021, to December 31, 2024. Diagnostic evaluation included symptom assessment, urinalysis, urine culture, inflammatory markers, pelvic contrast-enhanced computed tomography or computed tomography urography, and urine cytology, cystoscopy, or biopsy when clinically indicated. Cases were classified as definite or probable PD-(L)1-RC according to the strength of diagnostic evidence. Treatment response was recorded as supportive post-diagnostic evidence rather than a mandatory diagnostic criterion. Results The cohort included seven men and one woman, with a median age of 65 years (range, 36-69 years) and a median interval of 5 months (range, 2-36 months) from PD-1/PD-L1 inhibitor initiation to symptom onset. All patients had urinary frequency, urgency, and dysuria without fever. Urine cultures were negative and procalcitonin levels were normal in all patients; seven had leukocyturia, and imaging showed inflammatory bladder changes in all cases. One patient had patient-linked cytological, cystoscopic, and histopathological confirmation and was classified as definite PD-(L)1-RC. The remaining seven patients were classified as probable PD-(L)1-RC. All patients underwent ICI interruption or discontinuation and corticosteroid therapy, followed by symptomatic improvement. Exact CTCAE grade, time to symptom relief, steroid taper duration, ICI rechallenge outcome, and recurrence status were not uniformly documented. Conclusions PD-(L)1-RC should be considered in patients receiving PD-1/PD-L1 inhibitors who develop new urinary frequency, urgency, dysuria, sterile pyuria, or hematuria. The seven probable cases in this series were not pathologically confirmed and should be interpreted cautiously. Diagnosis requires structured exclusion of infection, malignancy, radiation injury, stones, urinary tuberculosis, and drug-related cystitis. The proposed diagnostic approach is preliminary and requires multicenter validation.